Social media adoption: The role of media needs and innovation characteristics - Zolkepli, I.A.; Kamarulzaman, Y. (Elsevier, 2015)
This research is designed to empirically investigate how social media needs and innovation influence the adoption of social media amongst Internet users. The theoretical perspective of the uses and gratifications, and Rogers' five characteristics of innovation are reviewed and extended to explain the needs and motivations of the consumer. The study is conducted by testing and quantifying the relationship between the uses and gratifications of social media, while taking into consideration the mediating effect of social media technology innovation. This research applies a two-phase, multimethod strategy in the context of Malaysia. The strategy comprises the qualitative approach via focus group discussions (FGDs) with 48 respondents and the quantitative approach via online survey questionnaires with 428 respondents. Overall, the findings suggest that social media adoption is significantly driven by three types of need category - personal (consisting of enjoyment and entertainment), social (consisting of social influence and interaction) and tension release (consisting of belongingness, companionship, playfulness). In turn, these needs are motivated by the social media innovation characteristics (relative advantage, observability, compatibility) that increase the likelihood of the adoption. The research makes a significant contribution in the area of media and technology adoption, which can be used to help marketers understand the factors that motivate social media usage, particularly the UXDs in designing human-computer interaction strategies.